A P-element insertion screen identified mutations in 455 novel essential genes in Drosophila. - Oh, S.W.; Kingsley, T.; Shin, H.H.; Zheng, Z.; Chen, H.W.; Chen, X.; Wang, H.; Ruan, P.; Moody, M.; Hou, S.X. (Genetics, 2003)
With the completion of the nucleotide sequences of several complex eukaryotic genomes, tens of thousands of genes have been predicted. However, this information has to be correlated with the functions of those genes to enhance our understanding of biology and to improve human health care. The Drosophila transposon P-element-induced mutations are very useful for directly connecting gene products to their biological function. We designed an efficient transposon P-element-mediated gene disruption procedure and performed genetic screening for single P-element insertion mutations, enabling us to recover 2500 lethal mutations. Among these, 2355 are second chromosome mutations. Sequences flanking >2300 insertions that identify 850 different genes or ESTs (783 genes on the second chromosome and 67 genes on the third chromosome) have been determined. Among these, 455 correspond to genes for which no lethal mutation has yet been reported. The Drosophila genome is thought to contain approximately 3600 vital genes; 1400 are localized on the second chromosome. Our mutation collection represents approximately 56% of the second chromosome vital genes and approximately 24% of the total vital Drosophila genes.